AKSI GOTONG ROYONG GENERASI MUDA UNTUK MENGURANGI GULMA DEMI KELESTARIAN KAMPUS - Mujito, Mujito; Tirta Jagad Dhita, Muhamad Ricky; Suwito, Suwito; Sulani, Sulani; Jahroni, Jahroni (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The presence of weeds in the campus environment not only reduces aesthetics but also inhibits the growth of main plants through nutrient competition. This program aims to restore the beauty and aesthetics of the campus, as well as foster an environmentally conscious character in the younger generation through this collective action. The method used in this activity is Participatory Action Research (PAR), which involves active participation from students in planning, action, and observation. This technical implementation is carried out through a mutual cooperation mechanism that includes manual weed removal, sweeping, containerization into trash bags, weed waste processing, and weed transportation to the final disposal site. The results of the activity resulted in significant changes in the campus area environment looking neater, cleaner, and more beautiful. And it can be concluded that the participatory approach is effective in campus environmental management, and it is recommended that this action be carried out regularly to realize the vision of a green campus.